The use of anthropometric indices as an alternative guide to initiating antiretroviral therapy (ART) in children at the Mildmay Centre in Uganda - Nyakwezi, Sheila (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.